2005
DOI: 10.1111/j.1439-0507.2005.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis is no longer a rare finding in children

Abstract: Onychomycosis was considered uncommon in children. This survey was carried out to estimate the frequency of fungal nail infections in children and adolescents (0-18 years of age) attending our clinic in the last decade and gain more insight into the aetiology and clinics of this entity in the paediatric age group. This study is based on data obtained from 2320 children and adolescents suspected of superficial fungal infection. Onychomycosis was diagnosed in 99 cases, representing 19.8% of all mycologically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 15 publications
14
47
2
8
Order By: Relevance
“…Recently, however, 16~18 age group were also included in the subject of pediatric onychomycosis5-8,15,21.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, 16~18 age group were also included in the subject of pediatric onychomycosis5-8,15,21.…”
Section: Discussionmentioning
confidence: 99%
“…In the proximal subungual type of onychomycosis with paronychia, nail lesions are almost always caused by Candida species, mainly C. albicans, but other Candida species such as C. parapsilosis and C. tropicalis may also be implicated. Although most of the researchers have introduced dermatophytes as the most important causative agents of onychomycosis 4,7,[19][20][21] , studies carried out by other investigators have demonstrated a greater prevalence of candidas 17,21,39) . Yeast onychomycosis accounts for nearly half of all nail disorders 31) and 46.…”
Section: Discussionmentioning
confidence: 99%
“…Infrequent consultations by adolescents, pediatricians' lack of knowledge, or insufficient systemic examination of the nails are the possible factors leading to misdiagnosis. [3].…”
Section: Discussionmentioning
confidence: 95%